(untitled) (Scientific journal of the Fergana State University, 2023)
In the article, from the beginning of the new period of development of Uzbekistan to the present day, a wide range of reforms in the field of Youth Policy, their directions, improvement of legal foundations, as well as the modern state of family-neighborhood cooperation in solving youth problems have been studied.